CHARACTER EDUCATION AND CHILDREN'S MORAL DEVELOPMENT: A LITERATURE REVIEW - Marzuki Marzuki; Al-Amin (International Journal of Teaching and Learning, 2025)
This research reviews the literature related to character education and moral development in children, with the aim of understanding how moral values can be effectively transferred through formal and informal education. The study identified effective methods in character education, such as the use of moral stories, interactive discussions, and real-life examples from adults. Findings from various studies show that character education that is consistently implemented in the school curriculum has a significant positive impact on children's moral development, as seen in their daily behaviour and their ability to make ethical decisions. This study recommends closer collaboration between schools and families and the establishment of policies that support the integration of character education in the formal education system. Thus, character education can contribute to the formation of a generation that upholds moral and ethical values.